Ticagrelor monotherapy in patients at high bleeding risk undergoing percutaneous coronary intervention: TWILIGHT-HBR. (18th October 2021) - Escaned, Javier; Cao, Davide; Baber, Usman; Nicolas, Johny; Sartori, Samantha; Zhang, Zhongjie; Dangas, George; Angiolillo, Dominick J; Briguori, Carlo; Cohen, David J; Collier, Timothy; Dudek, Dariusz; et al.
Abstract: Aims: Patients at high bleeding risk (HBR) represent a prevalent subgroup among those undergoing percutaneous coronary intervention (PCI). Early aspirin discontinuation after a short course of dual antiplatelet therapy (DAPT) has emerged as a bleeding avoidance strategy. The aim of this study was to assess the effects of ticagrelor monotherapy after 3-month DAPT in a contemporary HBR population. Methods and results: This prespecified analysis of the TWILIGHT trial evaluated the treatment effects of early aspirin withdrawal followed by ticagrelor monotherapy in HBR patients undergoing PCI with drug-eluting stents. After 3 months of ticagrelor plus aspirin, event-free patients were randomized to 12 months of aspirin or placebo in addition to ticagrelor. A total of 1064 (17.2%) met the Academic Research Consortium definition for HBR. Ticagrelor monotherapy reduced the incidence of the primary endpoint of Bleeding Academic Research Consortium (BARC) 2, 3, or 5 bleeding compared with ticagrelor plus aspirin in HBR (6.3% vs. 11.4%; hazard ratio (HR) 0.53, 95% confidence interval (CI) 0.35–0.82) and non-HBR patients (3.5% vs. 5.9%; HR 0.59, 95% CI 0.46–0.77) with similar relative ( P interaction = 0.67) but a trend towards greater absolute risk reduction in the former [−5.1% vs. −2.3%; difference in absolute risk differences (ARDs) −2.8%, 95% CI −6.4% to 0.8%, P = 0.130]. A similar pattern was observed for more severe BARC 3 or 5 bleeding with a larger absolute risk reduction in HBR patients (−3.5% vs. −0.5%; difference in ARDs −3.0%, 95% CI −5.2% to −0.8%, P = 0.008). There was no significant difference in the key secondary endpoint of death, myocardial infarction, or stroke between treatment arms, irrespective of HBR status. Conclusions: Among HBR patients undergoing PCI who completed 3-month DAPT without experiencing major adverse events, aspirin discontinuation followed by ticagrelor monotherapy significantly reduced bleeding without increasing ischaemic events, compared with ticagrelor plus aspirin. The absolute risk reduction in major bleeding was larger in HBR than non-HBR patients. Graphical Abstract: